Ewolucja Strategii lizbońskiej - wyzwania dla Polski - Płowiec, Urszula (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The Lisbon Strategy was a complex programme of improving the competitiveness of member states economies. The primary challenges for Poland, resulting from the Lisbon Strategy, are the same as for "old" member states of the European Union. But the level of challenge is higher because of unemployment and lower level of development. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1147, s. 294-306